Learning autonomy: higher education reform in Kazakhstan - Hartley, Matthew; Gopaul, Bryan; Sagintayeva, A.; Apergenova, Renata (Higher Education, 2015)
Higher education is a key economic and social priority in the global arena. Many countries have sought to advance reforms aimed at increasing access, promoting greater educational quality, and ensuring financial responsibility and sustainability. Often, strategies for achieving these aims are informed by experiences elsewhere. However, transporting education policy reforms can be problematic. Kazakhstan, a signatory of the Bologna Process, offers an example of a country seeking to improve student access and success and promote greater fiscal efficiency to advance the overall quality of its higher education system (Merrill in Int High Educ 59:26–28, 2010). A key strategy for achieving these goals is through reforms in university governance. In Central Asia, policy makers advance education reforms in order to accomplish several goals, including meeting “the new demands of ethnic nationalism, a globally competitive economy, and a labour market freed from administrative control” (Anderson and Heyneman 2005, p. 361). In Kazakhstan, policy makers have concluded that a system predicated on decentralized control with greater institutional autonomy (and accountability), along the lines of the US system, offers a promising strategy for improving the overall quality of its higher education system. This research collected on-site data on Kazakhstani higher education and presents the most recent data since efforts from OECD and World Bank in 2006 [OECD in Higher education in Kazakhstan (reviews of National Policies for Education). OECD, Paris 2007]. This research utilized semi-structured interviews with senior higher education administrators (53), members of the Ministry of Education and Science (6), a representative from the government (1), and experts from the World Bank (2) for a total of 62 participants. The results of the study show that academic leaders in Kazakhstan want greater autonomy. However, there is no clear consensus about what level of fiscal and academic autonomy is desirable and whether all institutions are prepared to manage themselves without Ministerial oversight. The roles of key constituents in academic governance have also not yet been clearly defined.
Keywords: autonomy; governance; higher education reform; Kazakhstan